MINDFULNESS, SELF-COMPASSION AND PERFECTIONISM AMONG DOCTORS - Adnan Haider,; Haiqa Khan,; Chen-Yuan Hsu, (PEOPLE: International Journal of Social Sciences, 2026)
The main objectives of present study were to find out relationship among mindfulness, self-compassion and perfectionism among doctors as well as demographics differences such as age, gender, and education on these variables. Three instruments; The Mindful Attention Awareness Scale (MAAS) (Brown& Ryan, 2003). Self-compassion Scale (Neff, 2003) and The Big Three Perfectionism Scale– Short Form (BTPS-SF) were administered on a conveniently selected sample (N=400) doctors along with demographic sheet and informed consent form. Results revealed that mindfulness has positively correlated with self-compassion and, and negatively correlated with perfectionism. Whereas mindfulness has non-significant negative relationship with perfectionism through correlation’s t-test analysis revealed that mean scores of mindfulness and perfectionism are high among males and mean scores of self-compassions are high among females. The analysis revealed that mean scores of mindfulness self-compassion and perfectionism are high in MBBS students than FCPS.